Factors Associated with Work Fatigue among Nurses in South Tangerang City Public Hospital - Haris Muzakir; Andra Vidyarini Vidyarini (Jurnal Cakrawala Promkes, 2023)
Work fatigue is a pervasive issue that affects nursing care quality and patient safety in healthcare settings. This study examined the prevalence of work fatigue among nurses and its association with various factors, including age, body mass index (BMI), work tenure, and work shift. This study employed a cross-sectional quantitative approach and was conducted at the South Tangerang City Public Hospital from February to March 2023. A total of 85 nurses participated in this study. The Industrial Fatigue Research Committee (IFRC) instrument was used to measure work fatigue, encompassing general, mental, and physical domains. Workload-related symptoms were assessed using Likert scale-based responses, classifying the respondents into fatigue and non-fatigue groups. The results indicated that 55.3% of the nurses reported experiencing work fatigue. Significant associations were observed between work fatigue and several other factors. Older nurses demonstrated a lower prevalence of work fatigue (PR:0.579; 95% CI: 0.415–0.808), suggesting that age is a protective factor against fatigue. Conversely, nurses with non-normal BMI exhibited a higher prevalence of work fatigue (PR: 1.587; 95% CI: 1.100–2.291). A longer work tenure was associated with increased work fatigue (PR: 1.851, 95% CI: 1.298–2.639), possibly due to cumulative stress and physical demands. Furthermore, night-shift nurses experienced higher work fatigue (PR: 1.882, 95% CI: 1.302–2.721) than day-shift nurses, indicating the disruptive impact of irregular sleep patterns. These findings emphasize the need for healthcare organizations to address work fatigue among nurses. Strategies may include workload management, providing resources for emotional support, and promoting a healthy work environment. Addressing the specific vulnerabilities of younger nurses, individuals with non-normal BMI, and working night shifts is vital for mitigating work fatigue